Assessment of pollution of Azov sea bottom sediments with heavy metals - M. V. Bufetova (Известия высших учебных заведений: Геология и разведка, 2016)
The assessment of the state of pollution of Azov sea bottom sediments with heavy metals - Pb, Cd, Cu, Zn, and Hg using the data of «Azovmorinformtsentr» (concentration of heavy metals in bottom sediments in 2010-2014) and published data for 1991-2009 is shown. The highest Pb concentrations (22 to 23 ґg/g for the allowable concentration of 85 ґg/g) were observed in the Taganrog Bay and the sea itself in the mid and late 90-s. In 2014 the maximum concentration in sediments was 44 ґg/g with an average concentration actually in sea equal to 10 rg/g. In 2013-2014 excess of permissible concentrations for Cd of 1,5 ґg/g was documented. Exceeding of the permissible level of Cu (38 rg/g for the allowable concentration of 35 ґg/g) was observed in the period from 1992 to 2005, as in the Taganrog Bay and around the sea. In 2014, the concentration of Cu over the entire area of the sea was still high - 30,2 ґg/g. In the 90-s in the sea of Azov there was a high Zn concentration (104 ґg/g), in 2014 - 48-50 ґg/g, a maximum of 130 rg/g (aliowable - 140 ґg/g). In bottom sediments of the Azov sea there are not the high concentrations of Hg, the maximum content was observed in the 90-s, then the concentration declined and in 2014 does not exceed 0,041 ґg/g (maximum of 0,3 ґg/g).